Impact of Circuit Training on Front Kick Accuracy in PSHT Students at Undana and STIM Commissariats, Kupang (NTT) - Kornelia K. Ola Tanaboleng; Ronald Dwi Ardian Fufu; Maria Andriani Barek Ladjar (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Objectives. This study aimed to examine the effect of circuit-based accuracy training on front kick accuracy among pencak silat athletes (PSHT) in Kupang, NTT. Materials and Methods. A one-group pre-test–post-test experimental design was applied. Thirty students (n = 30) were selected from a population of 33 across two PSHT branches (Undana and STIM Commissariats). Front kick accuracy was measured using a zoned target board with 20 kick attempts per participant. The intervention was implemented for two weeks, using 3–4 sets per session and a work duration of 30–45 seconds at each station. Data were analyzed using a paired-sample t-test with a significance level of p < 0.05. Results. Pre-test scores mostly fell within the moderate to good categories (28–36 points). After the intervention, post-test scores increased to 37–47 points, with all participants reaching the good to very good categories. The paired-sample t-test indicated a statistically significant improvement in front kick accuracy after the circuit-based training (p < 0.05). Conclusions. Circuit-based accuracy training effectively improves front kick accuracy in pencak silat athletes and may be recommended as part of technical training programs in martial arts. However, the findings are limited by the small sample and the inclusion of only two PSHT branches, which may reduce generalizability due to differences in coaching, facilities, and athlete backgrounds. Future research should involve larger and more diverse samples, longer intervention durations, and additional biomechanical or kinematic measurements to clarify the mechanisms underlying accuracy improvements.